The discourse of love in colombian massmedia; a story of symbolic violence (1993)
This paper presents some conclusions from a research project on the discourse of love in Colombian mass-media (radio. press, T.V., and advertising). Starting from a semiological analysis of more than a hundred discourses, this study attempts to uncover the constituent elements of the dynamics currently at work in love and, thus, to contribute to the establishment of a social diagnosis of the present phase of the history of Colombia. In fact, the discourse on love transmitted by the media, in its own way, reinforces the present culture of intolerance, indifference and violence. Finally, this paper proposes some alternatives that could be useful for delocalizing love and its discourse in the field of the utopias.